Genetic investigations on 8 patients affected by ring 20 chromosome syndrome - Giordano Lucio; Accorsi Patrizia; Finelli Palma; Marchi Margherita; Camporeale Nicole; Russo Silvia; Recalcati Maria; Ballarati Lucia; Vignoli Aglaia; Giardino Daniela; La Briola Francesca; Chiesa Valentina; et al. (BMC, 2010)
Abstract Background Mosaic Chromosome 20 ring [r(20)] is a chromosomal disorder associated with a rare syndrome characterized by a typical seizure phenotype, a particular electroclinical pattern, cognitive impairment, behavioural problems and absence of a consistent pattern of dysmorphology. The pathogenic mechanism underlying seizures disorders in r(20) syndrome is still unknown. We performed a detailed clinical and genetic study on 8 patients with r(20) chromosome, aimed at detecting the genetic mechanism underlying r(20) syndrome. Methods We submitted 8 subjects with a previous diagnosis of ring 20 chromosome mosaicism to a clinical re-evaluation, followed by cytogenetic, FISH, array-CGH and molecular analyses. The genetic study was also extended to their available parents. Results FISH and array-CGH experiments indicate that cryptic deletions on chromosome 20 are not the cause of the r(20) chromosome associated disease. Moreover, no evidence of chromosome 20 uniparental disomy was found. Analysis of FISH signals given by variant in size alphoid tandem repeats probes on the normal chromosome 20 and the r(20) chromosome in the mosaic carriers suggests that the r(20) chromosome is the same chromosome not circularized in the "normal" cell line. Conclusions Higher percentages of r(20) chromosome cells were observed to be related with precocious age at seizure onset and with resistance to antiepileptic drug treatment. Behavioural problems also seem to be associated with higher percentages of r(20) chromosome cells. Our results suggest that an epigenetic mechanism perturbing the expression of genes close to the telomeric regions, rather than deletion of genes located at the distal 20p and/or 20q regions, may underlie the manifestation of r(20) syndrome.